Effect of Number of Probes on Spherical Near-Field Measurement System - Dongming Wei; Junwei Dong; Ravi Kumar Arya; Yida Fan; Shiyuan Kong; Lijuan Li (IEEE Access)
Multi-probe spherical near-field measurement systems offer significant advantages in antenna characterization but are constrained by a fixed number of probes. Determining the optimal probe count for such systems is challenging, as it directly impacts measurement accuracy, system complexity, and cost-effectiveness. This work explores using a robotic arm to replicate a multi-probe spherical near-field measurement system and demonstrates a method for determining the ideal probe count during system design.